Zum Problem der Tropengrenze in der Sahara - Lauer, Wilhelm; Frankenberg, Peter (ERDKUNDE, 1977)
The plant-geographical margin of the tropics is established with the help of a quantitative floristic method. On the basis of dominance spectra limits (hor-isoflors) are defined, which separate different floral regions from one another, thereby allowing a floristic division of the Sahara. One profile for each of the Hoggar and Tibesti mountains supplements the studies in terms of the vertical dimension. The limits arrived at in this way are correlated to climato logical parameters and explained in terms of the plant physiology. The paper concludes with a discussion on the plant-geographical dynamics of the individual geo-elements since the Pleistocene.